Dietary Behaviors and Cardiovascular Disease Risk Factors in Indonesia in the Context of the Nutrition Transition and the COVID-19 Pandemic - Anyanwu, Oyedolapo. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Nutrition Interventions, Communication, and Behavior Change.; Advisor: Sara Folta.; Committee: Elena Naumova, Fang Fang Zhang, Virginia Chomitz, and Kenneth Chui.; Keywords: Nutrition, Epidemiology, and Public health.